2014
DOI: 10.2174/1874076601406010001
|View full text |Cite
|
Sign up to set email alerts
|

Excitability of Spinal Neurons During a Short Period of Relaxation Imagery

Abstract: To study spinal neuron function during relaxation imagery, we analyzed F-waves of the left thenar muscles in 15 healthy subjects (9 males, 6 females; mean age, 27.9 ± 9.2 years) after stimulating the left median nerve at the wrist. Fwaves were recorded in a resting position and during and after a 1-min period of relaxation imagery; they were recorded immediately after and at 5, 10, and 15 min after the relaxation imagery period. Persistence, F/M amplitude ratio, and latency were analyzed from the recorded F-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Few studies have used relaxation imagery as a method for decreasing abnormal muscle tone. In our previous study, we investigated spinal neuron excitability in healthy subjects by measuring F-waves at rest and during a 1-min period of relaxation imagery [1] and found that relaxation imagery for 1 min did not decrease spinal neuron excitability [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have used relaxation imagery as a method for decreasing abnormal muscle tone. In our previous study, we investigated spinal neuron excitability in healthy subjects by measuring F-waves at rest and during a 1-min period of relaxation imagery [1] and found that relaxation imagery for 1 min did not decrease spinal neuron excitability [1].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we investigated spinal neuron excitability in healthy subjects by analyzing F-waves before, during, and after a 1-min period of relaxation imagery [1]. There were no significant differences in F-waves obtained at rest and during and after relaxation imagery.…”
Section: Introductionmentioning
confidence: 99%